High temperature corrosion-fatigue behavior of a shot peened nickel based superalloy. (October 2022) - Li, Yong; Cockings, H.; Mignanelli, P.M.; Whittaker, M.; Cockings, B.J.; Buckingham, R.; Bache, M.R.
Abstract: As turbine entry temperatures (TET) in modern gas turbine engines continue to increase, Type II hot corrosion has the potential to be a significant damage mechanism at turbine disk rims as temperatures approach 700 °C. Therefore, assessment of the effect of hot corrosion damage is essential. In the current research, low cycle corrosion-fatigue behavior of a newly developed polycrystalline nickel superalloy was investigated. The testing program involved consideration of the variations in fatigue life brought about by changes in surface condition when tested at 700 °C in a representative service environment. The high temperature corrosion-fatigue resistance behavior is compared with a previous generation alloy, and detailed fractography to identify the mechanisms of fatigue crack initiation is discussed. High temperature corrosion-fatigue behavior is also correlated to the shot peened work hardened layer. Highlights: A newly developed Ni-base super alloy for disk applications offers improved high temperature hot corrosion fatigue resistance. High temperature corrosion fatigue resistance under hot corrosion environment is shown to be sensitive to shot peening condition. Stress concentrations from hot corrosion pits exceed the surface roughness effect in development of fatigue crack initiation. A delay in the pit to crack transition stage is critically controlled by the depth of the work hardened layer.